Scuola di Economia dello Sviluppo Integrale: I.P.I. contro P.I.L. - Romeo Ciminello, Romeo (European Journal of Sustainable Development, 2017)
There are three levels of human development: social project, political project, economic project to reach " integral human development ". Lonergan theory: value is in the man self-conscious and humanly auto-proportioned. Value is not economic, is human and assumes the economy develops not already and on its own autonomous laws, but thanks to practice application of the ideas of man and his intelligence . Productivity system: " point-to-point, point-to-line and point-to- surface": no limit to the creativity of human being. Without human cooperation no ideas of economic development " because he dominates economic mechanisms through his intelligence his self- appropriation: his consciousness of being the subject. Good of order leads to integral human development, since economics becomes a human science related to political economy to achieve better conditions of standards of living for the whole of humanity. The aim: creation of a renewed “School of development economics”, based on the good of order for the integral development of all countries, different from last century ideas, because development is integrative , transparent and complete, refusing economic liberalism , and defined the "new name for peace" . Economy is a fact of life, is knowledge, so no more mere transfer of wealth: development comes from transfer of knowledge. Its vector characters : balanced, sustainable and durable. Let’s leave GDP as measure of country development for U.P.I. (Unexploited Potential Index ) in its human characters , animals and environment in which investment has to supply a planned social return.